3D‐printed SAXS chamber for controlled in situ dialysis and optical characterization. (25th May 2022) - Ehm, Tamara; Philipp, Julian; Barkey, Martin; Ober, Martina; Brinkop, Achim Theo; Simml, David; von Westphalen, Miriam; Nickel, Bert; Beck, Roy; Rädler, Joachim O.
Abstract : A 3D printed X‐ray chamber which allows for in situ exchange of buffer and in situ optical transmission spectroscopy is presented. Abstract : 3D printing changes the scope of how samples can be mounted for small‐angle X‐ray scattering (SAXS). In this paper a 3D‐printed X‐ray chamber, which allows for in situ exchange of buffer and in situ optical transmission spectroscopy, is presented. The chamber is made of cyclic olefin copolymers (COC), including COC X‐ray windows providing ultra‐low SAXS background. The design integrates a membrane insert for in situ dialysis of the 100 µl sample volume against a reservoir, which enables measurements of the same sample under multiple conditions using an in‐house X‐ray setup equipped with a 17.4 keV molybdenum source. The design's capabilities are demonstrated by measuring reversible structural changes in lipid and polymer systems as a function of salt concentration and pH. In the same chambers optical light transmission spectroscopy was carried out measuring the optical turbidity of the mesophases and local pH values using pH‐responsive dyes. Microfluidic exchange and optical spectroscopy combined with in situ X‐ray scattering enables vast applications for the study of responsive materials.